If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + -1bx + 3 = 5 Reorder the terms: 3 + ax + -1bx = 5 Solving 3 + ax + -1bx = 5 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + ax + -3 + -1bx = 5 + -3 Reorder the terms: 3 + -3 + ax + -1bx = 5 + -3 Combine like terms: 3 + -3 = 0 0 + ax + -1bx = 5 + -3 ax + -1bx = 5 + -3 Combine like terms: 5 + -3 = 2 ax + -1bx = 2 Add 'bx' to each side of the equation. ax + -1bx + bx = 2 + bx Combine like terms: -1bx + bx = 0 ax + 0 = 2 + bx ax = 2 + bx Divide each side by 'x'. a = 2x-1 + b Simplifying a = 2x-1 + b Reorder the terms: a = b + 2x-1
| 5y=-45 | | 14x-28=-12-2x | | -2x+4y=10x-8 | | 0.04x+0.03=0.02x+1.05 | | (2x+15)+(4x-33)=90 | | y=-1/2x-6 | | M^2-10=-3m | | -13-1/4h+7 | | 0.5x=x+2 | | 6(3x-4)=5(4x-2) | | 6(x)+4= | | A*4/2=10.8 | | 3(g+4)=12 | | 3y+2x-2y=5 | | 9c=8+3c | | (4-3i)(-5+4i)= | | A=a+3b+2c | | -(1+6n)=31-2n | | 7+2=2+7 | | -4(5+a)=-4 | | -5x+7.5x=-10 | | 18=2y-6x | | 3x+27-x+45=2 | | 8(b)-4= | | 9x-5x-8x=4x-8 | | -53.9=(12+y)-7.7 | | X+2y=84 | | 0=(x-x^2) | | 2(9m)+10= | | -24=-4(5+t) | | -17+5r=-3(r+3) | | 50+22/16x=100 |